A Cystic Granulosa Cell Tumor of Ovary: An Incidental Finding in a 50 years Old Lady - Agarwal, Padam Kumari; Varshney, Nidhi; Maurya, Shyam Kumar (Annals of Pathology and Laboratory Medicine, 2018)
Granulosa cell tumours (GCTs) are rare ovarian sex cord stromal tumours. GCTs usually are oestrogen producing neoplasms and hence consequently, symptoms related to hyperestrogenism are common at the time of diagnosis. Here we document a case of cystic GCT that was incidentally discovered on histopathological examination. An abdominal hysterectomy was done for abnormal uterine bleeding in a 50 years old lady, clinically was thought to be due to uterine fibroid. A unilateral oophorectomy was also done due to a small cyst in the left ovary, which on histopathological examination revealed cystic granulosa cell tumour in the ovary. Equipped with this knowledge, a better clinical correlation with the presenting symptoms could be made in future by clinicians and pathologists. The final diagnosis may change the prognosis and also the future treatment plan.